Baumgartner : a novel - Auster, Paul, 1947- (New York : Grove Press, 2023)
"Paul Auster's brilliant eighteenth novel opens with a scorched pot of water, which Sy Baumgartner--phenomenologist, noted author, and soon-to-be retired philosophy professor--has just forgotten on the stove. Baumgartner's life had been defined by his deep, abiding love for his wife, Anna, who was killed in a swimming accident nine years earlier. Now 71, Baumgartner continues to struggle to live in her absence as the novel sinuously unfolds into spirals of memory and reminiscence, delineated in episodes spanning from 1968, when Sy and Anna meet as broke students working and writing in New York, through their passionate relationship over the next forty years, and back to Baumgartner's youth in Newark and his Polish-born father's life as a dress-shop owner and failed revolutionary. Rich with compassion, wit, and Auster's keen eye for beauty in the smallest, most transient details of ordinary life, Baumgartner asks: Why do we remember certain moments, and forget others?"--
Keywords: Widowers -- Fiction; Older men -- Fiction; College teachers -- Fiction; Wives -- Death -- Fiction; Grief -- Fiction; Novels